FACTORS INFLUENCING VALUE ADDED TAX IN DEVELOPING COUNTRIES: Received: 24th November 2024 Revised: 12th December 2024, 14th December 2024 Accepted: 10th December 2024 - Bujupi , Mjellma (PEOPLE: International Journal of Social Sciences, 2024)
This paper examines the influence of different VAT components, specifically VAT inside the country and VAT at the border on the overall VAT as a percentage of GDP in Kosovo from 2002 to 2022. Using multiple linear regressions, the analysis finds that both VAT inside and VAT at the border strongly correlate with the total VAT revenue as a percentage of GDP. However, VAT at the border has a slightly more significant impact, suggesting a higher dependence on VAT collected through imports. These findings imply that policies aimed at increasing exports while reducing imports could enhance local production and, consequently, economic growth. The study is limited by its focus on VAT components without considering other economic factors or countries. Nevertheless, the results provide valuable insights for policymakers and researchers interested in optimizing tax revenue strategies.